Effects of extracellular matrices on porcine umbilical cord matrix stem cells - Bryan, Kelley Elizabeth (Kansas State University, 2008)
The three transcription factors, Nanog, Oct-4 and Sox-2, are central regulators of pluripotency in embryonic stem cells. Porcine umbilical cord (PUC) matrix stem cells also express these transcription factors. Wharton’s jelly is composed of an extracellular matrix high in hyaluronic acid and various collagens and serves as a reservoir for several growth factors and cytokines. We expect that Wharton’s jelly includes a stem cell niche that provides a microenvironment that maintains and supports the stem-cell characteristics of PUCs. The mechanisms by which the PUCs remain primitive within the Wharton’s jelly are unknown. We developed methods for producing an extracellular matrix product extracted from porcine Wharton’s jelly that we named Pormatrix (PMX). When PMX is incubated at 37[degrees]C, it becomes a matrical gel that provides a matrix allowing PUC attachment and growth. Concentrating the protein in PMX by filtration provides a low molecular weight by-product which we refer to as flow through (FT). In Experiment 1, PUCs were seeded on Pormatrix, Matrigel or plastic substrates in the presence or absence of FT. PUCs cultured on Matrigel, Matrigel+FT, Plastic+FT and PMX had higher expression of Nanog compared to PUCs cultured on PMX+FT (P-value <0.05). In Experiment 2, the PMX and Matrigel were diluted to low protein concentrations (1.2-1.5 mg/ml protein) so that gelling did not occur. Adding FT to PMX, Matrigel and plastic increased gene expression of Nanog 2.78 fold compared to treatments without FT (P =0.10). Sox-2 expression was increased by adding FT to Matrigel but adding FT to the other matrix proteins had no effect resulting in a tendency for a matrix*FT interaction(P=0.10). The transcription factor Oct-4 remained unchanged regardless of treatment. To evaluate the effects of in vitro maintenance on Nanog, Oct-4 and Sox-2 we measured the relative gene expression in PUCs over the first six passages in vitro. Nanog, Oct-4 and Sox-2 did not differ over these passages. This may indicate that during the first six passages in vitro, PUCs remain relatively primitive. In summary, we prepared an extract from Wharton’s jelly from porcine umbilical cords. The extract supported PUC attachment and growth and appeared to regulate gene expression. Perhaps with further investigation the interactions of PUCs with their in vivo environment can be elucidated.
Keywords: Umbilical cord matrix stem cells; Porcine; Extracellular matrices; Cell culture; Agriculture, Animal Culture and Nutrition (0475)